MacOS High Sierra : the missing manual : the book that should have been in the box - Pogue, David, 1963- (O'Reilly Media, 2018)
With High Sierra, Apple has taken its macOS operating system to new heights. From Apple's efficient new file system to improved video streaming and support for virtual reality, this latest macOS version provides features improve your experience. And once again, David Pogue brings his humor and expertise to the #1 bestselling Mac book. Whether you're a developer or a home-user, this guide offers a wealth of detail on Apple's macOS 10.13 operating system, this new edition covers everything High Sierra has to offer. Perfect for newcomers. Get crystal-clear, jargon-free introductions to the best and brightest macOS apps, including Siri, Safari, iCloud, FaceTime, and AirDrop. Get the whole picture. Learn more efficient ways to navigate, organize, and edit your photos with new features in the Photos app. Go in-depth. Take advantage of Apple's new graphics technology, and its support for virtual reality. Gain real insight. David Pogue doesn't just tell you how to use macOS features. You'll also learn why to use them--and how to avoid common pitfalls.